Impact of generalized joint hypermobility on quality of life and physical activity in school-aged children: a longitudinal study - Oluwakemi A. Ituen; Christie D. Akwaowo; Gillian Ferguson; Jacques Duysens; Bouwien Smits-Engelsman (BMC Musculoskeletal Disorders)
Abstract Background Generalized Joint Hypermobility (GJH) offers flexibility that could enhance motor activities. However, if it leads to injury and pain, it increases functional difficulties and activity limitations. The far-reaching consequences of activity limitations and restricted participation include poor physical fitness and diminished quality of life. This study investigated whether variations in joint mobility are associated with physical activity levels, physical fitness, and overall quality of life (QoL) among children and whether these factors change over a 2-year period. Method One hundred and sixty-five school-aged children were recruited at the beginning of a two-year longitudinal study. One hundred and eleven children were measured three times at one-year intervals. Joint mobility was classified as normal mobile, mobile, or hypermobile. The children were administered the FACES pain scale, the child activity limitation interview, a physical activity questionnaire, and the pediatric quality of life inventory questionnaire. Additionally, the 20-meter shuttle run was used to estimate aerobic fitness. Results In this study, pain was unrelated to joint mobility. The activity limitations of our study population were not different at baseline or at the end of the study, irrespective of joint mobility. Children with GJH had significantly lower physical activity levels at the end of the study. Overall, QoL increased over time, and aerobic capacity decreased. However, changes in children with GJH were not significantly different from those in children with normal mobility in this respect. Conclusion Children with GJH were moderately active, however significantly less than children with normal mobility. Joint mobility had no significant effect on activity limitations, physical fitness or QoL.